Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.21037/gs-22-413
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the neutrophil-to-lymphocyte ratio and clinicopathological parameters in epithelial ovarian cancer patients and its effect on prognosis—a retrospective cohort study

Abstract: Background: Ovarian cancer is a common malignant tumor of the female reproductive system, and its mortality rate is high. In recent years, studies have found that the neutrophil-to-lymphocyte ratio (NLR) has a correlation with the prognosis of patients with malignant tumors; however, its association with the prognosis of ovarian cancer patients has not been studied. Therefore, we designed this study to investigate the correlation between the NLR and clinicopathological parameters in patients with epithelial ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Similarly, in China, researchers observed a correlation between NLR and stage, and that ovarian cancer patients with high NLR had a shorter postoperative PFS and a higher mortality rate. 36 Furthermore, Williams reported that in 519 ovarian cancer patients, elevated NLR not only indicated a poor prognosis but also had an association with clinical-pathological features of the disease such as stage, grade, and presence of ascites. 37 Likewise, Zheng-Feng observed that elevated NLR was linked to advanced stage, CA 125 elevation, and ascites, and that it could predict the feasibility of cytoreduction.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in China, researchers observed a correlation between NLR and stage, and that ovarian cancer patients with high NLR had a shorter postoperative PFS and a higher mortality rate. 36 Furthermore, Williams reported that in 519 ovarian cancer patients, elevated NLR not only indicated a poor prognosis but also had an association with clinical-pathological features of the disease such as stage, grade, and presence of ascites. 37 Likewise, Zheng-Feng observed that elevated NLR was linked to advanced stage, CA 125 elevation, and ascites, and that it could predict the feasibility of cytoreduction.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 , 17 ] In addition, MPV, NLR, and PLR may change during ovarian cancer treatment, and these changes may provide information about treatment efficacy and prognosis. [ 18 ] For example, decreases in MPV, NLR, and PLR values after treatment indicate that the cancer is in remission and is effective. It was emphasized that NLR and PLR were associated with both overall survival (OS) and progression-free survival (PFS), and as these rates increased, OS and PFS were also associated with shortening.…”
Section: Discussionmentioning
confidence: 99%